Kesehatan Mental Pengaruhnya Terhadap Pengembangan Kecerdasan Siswa di SMA Plus Riyadhul Jannah Cimenteng - Badru Sohim; Ajat Saputra; Ayi NajmulHidayat; Teti Ratnawulan (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study aims to determine the effect of mental health on the development of student intelligence at Riyadhul Jannah Cimenteng High School. Mental health is a psychological condition that plays an important role in the learning process and the development of student potential. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation of 10 students, counseling teachers, and school academic data. The results showed that students with good mental health have more ability to manage emotions, establish positive social relationships, and show stable academic performance. In contrast, students who experience psychological disorders such as anxiety and social pressure tend to experience learning difficulties and decreased motivation. The discussion is linked to Maslow's theory, Gardner's multiple intelligences, as well as an Islamic perspective that emphasizes the importance of peace of mind as the basis of intelligence. Thus, mental health is proven to play a significant role in shaping students' overall intelligence, both emotional, interpersonal and academic. This study recommends the need for interventions based on counseling, spirituality, and character education in schools.